2013
DOI: 10.1371/journal.pone.0082465
|View full text |Cite
|
Sign up to set email alerts
|

The A930G Polymorphism of P22phox (CYBA) Gene but Not C242T Variation Is Associated with Hypertension: A Meta-Analysis

Abstract: BackgroundRecently, it has been reported that the A930G and C242T polymorphisms within p22phox (CYBA) gene are involved in the pathogenesis of hypertension. However, the results remain controversial. Furthermore, no previous meta-analysis has been conducted to evaluate the relationship between the A930G and C242T polymorphisms and hypertension. Therefore, we performed this meta-analysis to clarify these controversies.Objective and MethodsAll of the included articles were retrieved from the PubMed and Embase da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…It has been observed that the -A930G polymorphism is associated with hypertension. Hypertensive patients with a GG genotype exhibit increased p22phox mRNA and protein levels and enhanced NAD(P)H oxidase activity compared with those with an AA or AG genotype, while no difference is observed in these parameters in healthy subjects (13).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has been observed that the -A930G polymorphism is associated with hypertension. Hypertensive patients with a GG genotype exhibit increased p22phox mRNA and protein levels and enhanced NAD(P)H oxidase activity compared with those with an AA or AG genotype, while no difference is observed in these parameters in healthy subjects (13).…”
Section: Introductionmentioning
confidence: 91%
“…There is accumulating evidence that the -A930G polymorphism of the p22phox subunit of NAD(P)H oxidases is associated with ICH (13). Membrane-associated NAD(P)H oxidases are the main enzymes responsible for ROS generation in neutrophil granulocytes and the vasculature, which may be important in the pathogenesis of ischemic injury and atherosclerosis (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, beginning in 2010 nine Chinese meta-analyses of the C242T polymorphism were published in relation with coronary artery disease (CAD) (Fang et al, 2010; Wu et al, 2013; Liang et al, 2014; Xu et al, 2014b; Hu et al, 2015), hypertension (Qin et al, 2013), atherosclerosis or diabetes and its complications (Li et al, 2015) and ischemic cerebrovascular diseases (Gu et al, 2013; Li et al, 2013). Three of them were associated with the analysis of A930G or A640G polymorphisms (Qin et al, 2013; Liang et al, 2014; Xu et al, 2014b).…”
Section: Single Nucleotide Polymorphisms and Associated Pathologiesmentioning
confidence: 99%
“…Three of them were associated with the analysis of A930G or A640G polymorphisms (Qin et al, 2013; Liang et al, 2014; Xu et al, 2014b). The results of these meta-analyses are summarized in Table 3.…”
Section: Single Nucleotide Polymorphisms and Associated Pathologiesmentioning
confidence: 99%